The Potential Impact of Childhood Traumatic Experiences on Coping Styles and Emotion Regulation of Nurse Practitioners During the COVID-19 Outbreak - Wang, Liyuanke; Zhang, Yan; Zhang, Xiaoli; Fan, Xiwang; Qiong, Luo; Hu, Chengping (Frontiers in Psychology, 2021)
Background: During an epidemic of a novel infectious disease, frontline medical staff suffer from high psychological stress. Previous studies have found that traumatic childhood experiences are associated with mental and physical health in adulthood. This study aims to explore the correlation between traumatic childhood experiences and coping styles among nurse practitioners. Method:This study sampled 278 nurse trainees from hospitals designated for the treatment of the novel coronavirus in Sichuan Province. The study measures included the Simplified Coping Style Questionnaire and the Childhood Trauma Questionnaire-Short Form. Results: Statistical analysis showed that there was no statistically significant difference in the general demographic data between the two groups. Conclusion: Childhood traumatic experiences have a significant impact on the active coping of nurse practitioners, and active coping may be emotionally protective for nurse practitioners.